Sustainable Optimization Model for Routing the Process of Distribution of Products, Pickup and Transport of Waste in the Context of Urban Logistics - Rodríguez Melquiades, José Antonio (2021)
Our gratitude to the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica - Fondecyt, for financing the research in progress.